Development of a Guidance and Counseling System (A Case Study: SMA Negeri 1 Binjai) - Eka Putri, Ranti; Tasril, Virdyra; Nadia Lestari, Ayu (Cattleya Darmaya Fortuna, 2024)
This study develops a web-based guidance and counseling system for high school students, focusing on enhancing previously existing features. One of the key features added is a chat function, which enables direct interaction between students and counselors to improve the effectiveness of guidance and consultation. Additionally, the system includes a student violation tracking feature, aimed at more effectively monitoring and addressing infractions. The research results indicate that this system can enhance the quality of guidance and counseling services in high schools by facilitating better communication and providing optimal support in handling violations. It is hoped that this study can contribute to the development of more effective guidance and counseling support systems within educational environments